Analisis Perlakuan Akuntansi Aktivitas Perkebunan Berdasarkan Implementasi PSAK 69: Studi pada PT Salim Ivomas Pratama TBK - Rahma Fatimah Santoso; Diana Zuhroh; Tjandra Wasesa; Wiratna Wiratna; Heri Tony (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This case study focuses on a company with a single object in the form of biological assets. This study seeks to evaluate the implementation of PSAK 69 at PT. Salim Ivomas Pratama Tbk, focusing on the recognition, measurement, and disclosure of biological assets, including oil palm and rubber trees, and assessing the extent to which PT Salim Ivomas Pratama Tbk applies PSAK 69 in accounting practices. This research method is descriptive qualitative analysis, with secondary data obtained through documentation methods and literature studies. The analysis involves explaining the reality of an object in narrative form based on data from the 2021-2022 financial statements of PT. Tunas Baru Lampung Tbk. The results of the study indicate that the SIMP Group has adopted PSAK 69 effectively in terms of recognition, measurement, and disclosure of agricultural products. However, there are differences in the application of entities to PSAK 69 relating to measurement and disclosure.